A study of dermatoglyphics in club foot - Ali, Sadakat; Arora, Mani; Sinha, Abhishek P.; Rohatgi, R. K. (International Journal of Research in Medical Sciences, 2017)
Background:Development of dermatoglyphics pattern is under genetic control and it is established that aetiology of club foot is partly environmental and partly genetic. So study of dermatoglyphics pattern in club foot patient may become a diagnostic tool to know the development & inheritance of this clinical disorder. Methods:A total of 42 male child aged b/w 1-8 year were included, for obtaining the palmar and finger tip print standard ink method suggested by Kilgariff was used, and each palmar and finger print were examined for important parameters like loops, whorls, arches, a-t-d angle, a-b ridge count and TFRC count. Then results were tabulated and analysed statistically. Results:Frequency of whorls increase in both hands significantly, frequency of arches and ulnar loops decrease significantly, frequency of radial loops increase in right hand and decrease in left hand but difference was not significant. TFRC count was reduced significantly and no significant difference was found in a-t-d angle and a-b ridge count. Conclusion: Dermatoglyphics is a genetically determined reliable marker for detecting the incidence of club foot. Merely by identifying the dermatoglyphics pattern of couples with family history of club foot may be at risk of having their offspring affected, and they can be diagnosed early and preventive measures can be taken.